Sheet resistance and surface topology time dynamics of intrinsic oxide film on InSe crystals - Katerynchuk, V.M.; Kovalyuk, Z.D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
It has been shown that a result of InSe crystal oxidation is formation of an
intrinsic oxide film that has not insulating but conductive properties. This conductive
film forms a potential barrier with the semiconductor substrate. Sheet resistance
measurements of the InSe oxide film in dependence on the oxidation time under various
temperature conditions were carried out. The resistance was also tested for oxide films
obtained for two mutually orthogonal crystal faces: perpendicular and parallel to the с
axis. It has been established that the film sheet resistance is substantially changed only
for 5 min of the oxidation time, and further oxidation does not affect its value that is
about 100-150 Ohm/square. Surface topology of InSe intrinsic oxide was studied using
the atomic-force microscopy method. It was found that this surface becomes
nanostructured and contains nanoneedles oriented perpendicularly to the plane of sample
surface. Dynamics of surface topology changes in dependence on temperature-time
conditions of the oxidation process has been ascertained. It manifests itself in a change of
lateral and vertical dimensions of nanoneedles as well as their density.